ANALISIS KEBUTUHAN STRATEGI PEMBELAJARAN UNTUK MENGEMBANGKAN KEPERCAYAAN DIRI BERKOMUNIKASI DALAM BAHASA INGGRIS PADA MAHASISWA PENDIDIKAN JARAK JAUH - Etika, Indah; Jasrial; Zen, Zelhendri; Yuniko, Fajrilhuda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Confidence in English communication is an important affective aspect that influences students’ willingness to participate and use English in learning activities. However, in distance higher education contexts, positive learning experiences do not always indicate that students have sufficient readiness to communicate confidently. This study aimed to analyze the learning strategy needs required to support the development of English communication confidence among distance education students. This study employed a quantitative descriptive design based on a needs analysis approach. The participants were 98 students of Universitas Terbuka enrolled in the English Communication course in 2026. Data were collected through a five-point Likert-scale questionnaire consisting of three constructs: affective barriers in English communication, learning experience, and learning support needs. Data were analyzed using descriptive statistics with the assistance of SPSS, including mean scores and reliability testing using Cronbach’s Alpha. The results showed that students perceived their English learning experience as very high (M = 4.55), with communication learning receiving the highest score (M = 4.68). Nevertheless, students still reported very high needs for learning support to develop communication confidence (M = 4.50). The highest needs were strategies or practices to reduce nervousness when speaking English (M = 4.53) and additional speaking practice (M = 4.52). These findings indicate that distance English learning design should not only focus on language competence but also address students’ affective readiness through supportive communication practices, gradual speaking activities, and constructive feedback.